Efeito de citocinas e toxina tetânica na vacinação gênica de tumores que expressam CEA com Scfv6C4 - Zanetti, Bianca Ferrarini [UNIFESP] (2017)
Introduction: Colon and rectum cancers are highly prevalent among men and women, and prevention and treatment are major medical and scientific challenges. Carcinoembryonic antigen (CEA) is the main tumor associated antigen of these cancers. Previously, our group developed a DNA vaccine against CEA-expressing tumors using a CEA surrogate, scFv6.C4, and its efficacy, evaluated in transgenic mice for CEA, showed 40% tumor-free animais by more than 100 days and in the others the survival increase was between 30 and 70% in relation to the non-vaccinated group. Objective: To evaluate the adjuvant effect of IFNy (Interferon Gamma), GM-CSF (Granulocyte Macrophage Colony-Stimulating Factor), FrC (Fragment C of Tetanus Toxin) and IDUA (Alpha-L-Iduronidase) in gene vaccination with scFv6.C4. Methods: C57BU6J-CEA2682 mice were immunized 4 times by intramuscular electroporation with the plasmid uP-PS/scFv6.C4 alone, or in combination with adjuvant vectors expressing FrC, GM-CSF, IFNy or IDUA. Vaccinated animais were challenged by subcutaneous injection of murine colon adenocarcinoma cells, MC38-CEA, and tumor growth was monitored. The humoral andcellular immune responses were accessed by ELlSA, immunocytochemistry, ELlSPOT, cell proliferation and cYt~toxicity assays. Results: Immunization with scFv6.C4 induced anti-CEA antibodies, with titre about 4- fold higher than preimmune serum. When challenged with MC38-CEA cells, approximately half of the immunized animais did not develop tumor during 80 days of observation, and the others had varying degrees of retardation in tumor growth. The adjuvants tested did not lead to a significant increase in antibody titer, however, animais immunized with scFv6.C4 and FrC or IFNy had increased survival. Cellular response assays showed a significant increase in cytotoxic cell response, especially in the animais vaccinated with FrC. Conclusions: Immunization with scFv6.C4 in combination with adjuvants FrC or IFNy elevated antitumor effect via increased cytotoxic cell response.